Pemeriksaan Payudara Sendiri (SADARI) dengan Stadium Kanker Payudara - Erin Desweni; Wirsma Arif Harahap; Afriwardi Afriwardi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
This study aims to determine the relationship between breast self-examination (BSE) and the stage of breast cancer at RSUP Dr. M. Djamil Padang in 2020. The method used is a mixed-method with a Sequential Explanatory Design. Sampling technique using Consecutive Sampling. Quantitative data was obtained through questionnaires and qualitative data using interviews. The results showed that the number of respondents who were not good at breast self-examination (BSE) was 64 (58.2%) and respondents who were good at breast self-examination (BSE) were 46 (41.6%). The most common breast cancer stages were at stage 3 of 67 (63.9%), stage 2 of 30 (27.3%) and the least at stage 4 was 13 (11.8%) with a p-value = 0.020. In conclusion, there is a relationship between breast self-examination (BSE) and the stage of breast cancer. Keywords: Breast Self-Examination (BSE), Breast Cancer Stage